An introduction to programming : - Wu, C. Thomas (McGraw-Hill, 1997)
This book includes numerous sample programs that vary in difficulty from easy to complex. It also covers both Java applications and applets; Lucid illustrations to explain concepts are presented in a clear and concise mannerThe author also discusses modern topics such as event-driven programming, graphical interface, object serialization.